Anti-glaucoma medications lowered decorin and altered profibrotic proteins in human tenon's fibroblasts. (November 2022) - Nikhalashree, Sampath; George, Ronnie; Shantha, Balekudaru; Vijaya, Lingam; Sulochana, Konerirajapuram Natarajan; Coral, Karunakaran
Abstract: Long term exposure to anti-glaucoma medications (AGMs) leads to an increase in extracellular matrix (ECM) accumulation in primary glaucoma patients. This study aims to evaluate the effect of topical AGMs in primary human tenon's fibroblasts (HTFs) and analyze the expression of profibrotic and anti-fibrotic proteins. Primary HTFs were cultured from patients undergoing cataract (control) and trabeculectomy. The different types of AGMs in single/multiple combinations (BB, PG, AA, CAI, CH, combinations of 3- PG + AA + CAI, 4A- BB + PG + AA + CAI, 4B– BB + PG + CAI + CH and 5- BB + PG + AA + CAI + CH) on chronic exposure were tested for cell viability using MTT assay and morphological alterations. Profibrotic proteins mainly SPARC, LOXL2, COL1A1 and anti-fibrotic DCN were analyzed in treated HTFs using q-PCR and ELISA. Sirius red staining and collagen gel contraction (CGC) assay were performed to assess collagen synthesis and the contractility of HTFs, respectively. Except for AA and CH, the other AGMs at a higher concentration were found to decrease the cell viability of HTFs. The morphology of HTFs were altered on exposure to BB, CH and AA; Profibrotic proteins i.e., SPARC, LOXL2 and COL1A1 were significantly increased (p < 0.05) on exposure to a combination of AGMs with TGF-β1, whereas the anti-fibrotic DCN expression was significantly lowered (p < 0.05) in single/multiple AGM exposure. Sirius red staining showed increased collagen synthesis with combinations of AGMs with TGF-β1. Meanwhile, HTFs showed increased collagen gel contraction with TGF-β1, CAI and CH. This study reveals that altered profibrotic proteins, with significantly lowered DCN on chronic exposure of AGMs in HTFs. Highlights: Profibrotic proteins were significantly increased with combination of AGMs in HTFs. The anti-fibrotic DCN was significantly lowered in HTFs with single/multiple AGM. Sirius red staining showed increased collagen synthesis with combinations of AGMs. HTFs showed increased collagen gel contraction with TGF-β1, CAI and CH.